The Development of Assalaam Observatory from the Perspective of Amin Abdullah's Mit Paradigm - Riadi, AR Sugeng (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
Indonesian Islamic boarding schools (pesantren) face modernization challenges demanding knowledge integration. Observatories are significant legacies of Islamic civilization, serving to study celestial bodies and strengthen faith. Pondok Pesantren Modern Islam Assalaam Sukoharjo became the first pesantren in Indonesia with an official observatory, inaugurated on July 6, 2015. This research analyzes how Observatorium Assalaam implements Amin Abdullah's Multidisciplinary, Interdisciplinary, and Transdisciplinary (MIT) paradigm, which rejects the dichotomy between religious and general sciences. Although the observatory development predates the formal MIT theory publication, the actions taken align with the paradigm. Observatorium Assalaam functions as a laboratory integrating natural sciences (astronomy) with Islamic sciences (fiqh and sociology) for determining the hijri calendar, qibla direction, prayer times, eclipse phenomena, and enhancing astronomical literacy among students and the public. Challenges include the absence of astronomy in formal curricula and shortage of human resources. Through this approach, Observatorium Assalaam strives to produce Muslims strong in faith, noble character, and expert in science and technology.